Governance of water resources for service managers in the province of Heredia, Costa Rica - Jimenez, Maria Alvarez (2023)
The effectiveness in governance and water management in different operating entities of the water service in the province of Heredia, Costa Rica is analyzed. It is postulated that the effectiveness of water management is a function of features of the governance model and professional and operational capabilities of the service. The objective is to help service operators increase the effectiveness and quality of their management and governance, service to users and the joint protection of water resources in the region. Seven cases corresponding to three management models were studied: two ASADAS, four municipal aqueducts and the Heredia Public Services Company (ESPH-SA). Qualitative information was compiled through interviews, consultations and surveys of administrators and documentary analysis. The information was classified and systematized in aspects related to governance and the management and operation of services. It is highlighted that the ASADAS base their effectiveness on the approach and knowledge of local needs and a sense of belonging despite resource limitations. The ESPH-SA in the organization processes and specialized businesses and in knowledge and information. Municipalities show marginal attention to their aqueducts, generating insufficiencies and service continuity deficiencies. Finally, the municipal aqueducts have the greatest need for transformation in their model. A joint strategy must be sought among the operators to invest in the protection of water resources in the recharge zones and in the aquifers of the region that they share.